Design of Metastable β-Sheet Oligomers from Natively Unstructured Peptide - Guerrero-Muñoz, Marcos J. (American Chemical Society, 2013)
[Image: see text] Amyloid oligomers represent the primary pathological species for neurodegenerative diseases such as Alzheimer’s and Parkinson’s diseases. Toxic oligomers are formed by many different proteins and peptides, but their polydispersity makes them highly dynamic and heterogeneous. One way to stabilize these structures is to prepare constrained peptides that can be used to study amyloid intermediates, to identify oligomer-specific drugs, and to generate conformational antibodies. These conformational antibodies have demonstrated that oligomers share a common epitope. In this research, we used a 40-amino acid unstructured segment of prion protein (Prp) 109–148 with substitutions of methionine for glycine (Prp-G) residues to prepare a stable and homogeneous population of β-sheet oligomer mimics. These structures were characterized by multiple biophysical and biochemical techniques that show characteristic features of oligomers. Finally, this preparation was not detected by three different sequence dependent prion antibodies.